Thiazides diuretics in the treatment of nephrolithiasis: are we using them in an evidence-based fashion? - Vigen, Rebecca (2010)
In the 1980s a change occurred in hydrochlorothiazide prescribing practices for hypertension from high-dose (50 mg/day) to low-dose (12.5–25 mg/day) therapy. However, randomized controlled trials (RCT) for prevention of calcium-containing kidney stones (CCKS) employed only high doses (≥50 mg/day). We hypothesized that these practices have resulted in underdosing of hydrochlorothiazide for prevention of CCKS. Patients with a filled prescription for thiazide diuretics that underwent a 24-h urine stone risk factor analysis were eligible. Those with evidence that thiazide was prescribed for CCKS were further analyzed. Of 107 patients, 102 were treated with hydrochlorothiazide, 4 with indapamide, and one with chlorthalidone. Only 35% of hydrochlorothiazide-treated patients received 50 mg/day; a dose previously shown to reduce stone recurrence. Fifty-two percent were prescribed 25 mg and 13% 12.5 mg daily, doses that were not studied in RCT. Evidence-based hydrochlorothiazide use was suboptimal regardless of where the patient received care (Nephrology or Endocrinology clinic). In a small subset of patients (n = 6) with 24-h urinary calcium excretion measured at baseline and after 2 hydrochlorothiazide doses (25 and ≥50 mg), there was a trend toward decreased urinary calcium excretion as the dose was increased from 25 to ≥50 mg/day (p = 0.051). Low-dose hydrochlorothiazide was often used for prevention of CCKS despite the fact that there is no evidence that it is effective in this setting. This may have resulted from a practice pattern of using lower doses for hypertension therapy or a lack of knowledge of RCT results in treatment of CCKS.